A Study of Crystallographic and DC Electrical Characteristics of PPy/Ag Nanocomposites - salman, mohammed abdilridha; Hassan, Salma M. (Iraqi Journal of Physics, 2021)
ABSTRACT: Polypyrrole and polypyrrole / silver nanocomposites were fabricated by in-situ polymerization employing Ammonium Persulphate as an oxidizing agent. Nanocomposites were synthesized by combining polypyrrole and silver nanoparticles in various weight percentages (0.1%, 0.5%, 3%, 5% and 7% wt.). Crystallographic data were collected using X-ray diffraction.  PPy particles were found to have an orthorhombic symmetry. In contrast, PPy/Ag nanocomposites were reported to have monoclinic structure. The crystallite size was determined by XRD using Scherrer equation and considered to be within 49 nm range. DC conductivity of pelletized samples was evaluated in the temperature range of 323.15k to 453.15k. The conductivity displayed an increase when the temperature is increased from 323.15k to 453.15k. Activation energies were determined from plots of Arrhenius for all nanocomposites. The findings indicated that the activation energy decrease with increasing the weight percentage of Ag nanoparticles in the nanocomposites.